Synthesis of 6-Bromo-7-Arylaminoisoquinoline-5,8-Quinones and Its Effects on Piscirickettsia Salmonis Infection in Vitro - Modak-Canobra, B; Ibacache-Rojas, J; Zapata-Ramirez, P; Espinoza-Lopez, M (John Wiley and Sons Inc, 2024)
Among the most important aquaculture resources for our country, salmon and trout stand out. Their production has increased significantly in recent decades, making them two of the most valuable resources in economic terms. However, high aquaculture production has allowed many pathogens to proliferate, causing infectious diseases and significant production losses. Piscirickettsia salmonis is a gram-negative, facultative intracellular bacterium that is responsible for causing severe disease in a variety of salmonid fish species. Despite the significant impact of P. salmonis on aquaculture, effective treatments for this disease remain limited. Current prevention and control strategies often include antibiotics and vaccines. However, these treatments have shown varying degrees of efficacy. A promising approach involves synthesizing bioactive analog compounds with antibacterial properties. Quinones, secondary metabolites that are abundant in nature, have become a focal point of interest due to their diverse physiological activities, including antibiotic, insecticidal, antifungal, and anticancer properties. In this study, it is shown the synthesis of series 6-bromo-7-arylaminoisoquinoline-5,8-quinones, the characterization of these compounds using classical spectroscopic methods such as one-dimensional nuclear magnetic resonance (NMR), FT-IR (infrared), mass spectrometry, and the biological activity against Piscirickettsia salmonis. The brominated derivative compounds showed no cytotoxicity at any concentration evaluated. Furthermore, the infectivity of P. salmonis after treatment with the analog compounds indicated that derivatives methyl 6-bromo-7-((4-methoxyphenyl)amino)-1,3-dimethy-5,8-dioxo-5,8-dihydroisoquinoline-4-carboxylate (4b) and methyl 7-((4′-amino-[1,1′-biphenyl]-4-yl)amino)-6-bromo-1,3-dimethy-5,8-dioxo-5,8-dihydroisoquinoline-4-carboxylate (4g) reduced the bacterial load at 25 μg/mL concentration. © 2024 John Wiley & Sons Ltd.